2008
DOI: 10.1590/s1676-06032008000400013
|View full text |Cite
|
Sign up to set email alerts
|

As borboletas (Lepidoptera, Papilionoidea) do Campus Universitário Darcy Ribeiro (Distrito Federal, Brasil)

Abstract: O cerrado brasileiro, considerado o segundo maior bioma do país em extensão territorial, encontra-se atualmente constituído apenas por fragmentos de vegetação que em conjunto representam menos de 20% de sua vegetação original. Neste trabalho nós investigamos a fauna remanescente de borboletas em fragmentos de cerrado sensu stricto e mata ciliar do campus universitário Darcy Ribeiro. No total foram encontradas 128 espécies correspondendo a aproximadamente 25% da fauna de borboletas do Distrito Federal. Alguns f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
1
7
2
4
Order By: Relevance
“…Morpho helenor , Siproeta stelenes , Heliconius erato , and Heliconius ethilla coincided with the study realized at the University Campus Darcy Ribeiro, in an urbanized area in the Federal District (Pinheiro et al 2008). These are typical species of riparian areas, a characteristic of the sample site.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Morpho helenor , Siproeta stelenes , Heliconius erato , and Heliconius ethilla coincided with the study realized at the University Campus Darcy Ribeiro, in an urbanized area in the Federal District (Pinheiro et al 2008). These are typical species of riparian areas, a characteristic of the sample site.…”
Section: Discussionsupporting
confidence: 75%
“…However, compared with records for several Brazilian states such as recorded by Isehard and Romanowski (2004), Marchiori and Romanowski (2006), Emery et al (2006), Dessuy and Morais (2007), Pinheiro et al (2008), Isehard et al (2010), Ritter et al (2011), Zacca and Bravo (2012), and Bogiani et al (2012), the number of species found is lower. This fact could very well be explained by the sampled area size and sampling effort (Table 4).…”
Section: Discussioncontrasting
confidence: 56%
“…M. helenor was one of the most abundant species in riparian forests in the Cerrado in the Parque Nacional da Serra do Canastra MG (Marini-Filho & Martins 2010), showing similar results to the ones in the present study. Species of the genus Morpho can fly in the understory or canopy, and M. helenor flies to about one meter above ground along streams and forest edges (De Vries et al 2010), being considered typical of riparian forest (Pinheiro et al 2008), which may explain the great abundance of this butterfly in APE Mutuca, having 79% of individuals sampled in this environment.…”
Section: Resultsmentioning
confidence: 99%
“…The APE Mutuca showed greater richness other places, such as APE Cercadinho in Belo Horizonte, a very similar and nearby area, where forty-five species ) were recorded; in Uberlandia, where thirty-six species were found in urban and extra urban areas (Fortunato & Ruszczyk 1997); in Jardim Botânico de Brasília, where forty-six species were recorded in riparian forest, Cerrado and transition area (Pinheiro & Ortiz 1992); and in riparian and Cerrado areas of Campus Darcy Ribeiro in Brasília, there were thirty-one species (Pinheiro et al 2008). The number of species found in the APE Mutuca was similar only to the Parque Nacional da Serra do Canastra (MG), where sixteen fragments of riparian vegetation were sampled, and sixty-seven species were registered (Marini-Filho & Martins 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, changes in habitat quality caused by deforestation, fire, and global climate change affect butterfly populations. The short life cycles of frugivorous butterflies also make them useful organisms for biomonitoring (Uehara-Prado and , Pérez et al 2017, Pinheiro et al 2008.…”
mentioning
confidence: 99%